Internalization of Multicultural Islamic Education in Pharmaceutical Vocational School, Medan City - Uswatun Dalimunthe; Azizah Hanum OK; Junaidi Arsyad (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Pharmacy Vocational High School is one of the educational institutions involved in the form of health services. Interdisciplinary knowledge is not enough. Pharmacy majors also emphasize developing potential in the technology for manufacturing, storing and supplying medicines. In the daily context, it also requires interaction in a multicultural environment and adheres to Islamic values. In general, Islamic teachings with a multicultural paradigm have been manifested in Islamic religious education which is explicitly expected to be implemented by all students in their professional world. This study uses a qualitative method with a descriptive approach. This research managed to find that; Islamic religious education with a multicultural paradigm has been successfully internalized through good interrelationships in the school environment, internalized values include tolerance (tasamuh), mutual assistance (ta'awun) and social harmony (tawazun), and moderation in religion (tawasuth). Furthermore, this study also found that the internalization of multicultural values goes through the stages of value transformation, value transactions, and trans-internalization of values that are manifested through teaching and cultivating by upholding tolerance.